Adoption of instant messenger: an empirical investigation - Tarofder, Arun Kumar; Sultana, Umme Salma; Md Yusoff, Siti Khalidah; Sherief, Sultan Rehman; Haque, A. K. M. Ahasanul (Lifescience Global, 2019)
Instant Messenger (IM) is one of the quickest developing intra-hierarchical innovations that have been changed organizational communication framework. Intuitiveness, sharing substance, diminishing reaction time are a couple of its attributes that charm the two people and associations. It has been accounted for that 63 per cent associations over the world have just been executed IM in their authoritative correspondence framework. Thus, a tremendous number of specialists have researched the possibility of IM as an intra-hierarchical correspondence framework. In light of the broad writing survey, a blended supposition can be found on the viability of IM over the globe, which in the end urges this examination to explore more inside and out. All the more particularly, this examination tries to explore the critical drivers of IM adoption in an organizational setting. Moreover, this examination likewise tries to give a superior understanding of the marvel of IM usage in various socioeconomics, for example, orgabnizational size and industry. An online structured questionnaire was produced to gather data. With three reminders, this study able to get responses from 197 respondents from 3 primary states in Malaysia. Results of this study uncovered that knowledge creation is the most vital driver for IM adoption followed by organizational pressure and relative advantage. Additionally, domination examination uncovered that the organizational pressure is moderately more imperative in Corporation than SMEs. So also, learning creation turns into the most essential driver for assembling industry and relative advantage circumstances for benefit. This finding, to be sure, gives rules to administrators on why associations ought to receive IM in their intra-hierarchical correspondence framework.